Advances in cellulosic conversion to fuels: engineering yeasts for cellulosic bioethanol and biodiesel production - Ko, Ja Kyong; Lee, Sun-Mi (CURRENT BIOLOGY LTD, 2018)
Cellulosic fuels are expected to have great potential industrial applications in the near future, but they still face technical challenges to become cost-competitive fuels, thus presenting many opportunities for improvement. The economical production of viable biofuels requires metabolic engineering of microbial platforms to convert cellulosic biomass into biofuels with high titers and yields. Fortunately, integrating traditional and novel engineering strategies with advanced engineering toolboxes has allowed the development of more robust microbial platforms, thus expanding substrate ranges. This review highlights recent trends in the metabolic engineering of microbial platforms, such as the industrial yeasts Saccharomyces cerevisiae and Yarrowia lipolytica, for the production of renewable fuels.
Keywords: ACETIC-ACID TOLERANCE; SACCHAROMYCES-CEREVISIAE; YARROWIA-LIPOLYTICA; XYLOSE ISOMERASE; DIRECTED EVOLUTION; LIPID PRODUCTION; RHODOSPORIDIUM-TORULOIDES; TRANSCRIPTION FACTOR; ETHANOL-PRODUCTION; FERMENTATION